EXAMINING THE RELATIONSHIP BETWEEN ACADEMIC ACHIEVEMENTS AND TIME MANAGEMENT SKILLS OF THE STUDENTS AT THE FACULTY OF SPORTS SCIENCES - Yildiz, Metin; Kirtepe, Abdurrahman; Baydili, Kürşad Nuri (Ataturk Universitesi, 2021)
The aim of this study was to compare the relationship between the time management skills of students studying at the faculty of sports sciences and their academic achievement according to different variables. The universe of the research consists of 1543 students studying at Fırat University, Faculty of Sport Sciences in the 2020-2021 academic year. The sample of the study was determined by convenience sampling method and consists of 265 participants, 152 males and 113 females. In the study, demographic characteristics of the participants were collected using the "Personal Information Form", and other research data were collected using the "Time Management Inventory(TMI)". Various statistical analyzes were applied to the data obtained from the participants via SPSS 25.00 software. Frequency and percentage values of categorical variables, arithmetic mean and standard deviation values of quantitative variables are presented. Independent sample t test was used to compare categorical variables with two categories and quantitative variables, and one-way Anova test was used to compare categorical variables with more than two categories and quantitative variables. If a significant difference was found in the one-way Anova test, the categories were compared in pairs using the Bonferroni test. As a result of the findings obtained; while it has been observed that male students are more successful in time planning, female students are not interested in efforts to waste time that will waste their time, students who study in the recreation department have more command of time attitude in connection with the department they study, students who participate in physical-sports activities in their free time, devote their time to these activities. It was observed that they performed their time planning better, and there was no significant relationship between students' academic grade point averages and their time management skill levels. © 2021, Ataturk Universitesi. All rights reserved.
SPOR BİLİMLERİ FAKÜLTESİNDE OKUYAN ÖĞRENCİLERİN ZAMAN YÖNETİM BECERİLERİ İLE AKADEMİK BAŞARILARI ARASINDAKİ İLİŞKİNİN İNCELENMESİ
Keywords: Academic; Student; Time; Time Management